Handbook of research on administration, policy, and leadership in higher education - Mukerji, Siran (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, [2017], 2017)
This book offers the latest scholarly research on contemporary management issues in educational institutions and presents best practices to improve policies and retain effective governance, addressing the current state of higher education at an international level"--Provided by publisher. Content Notes: Strategic leadership development in research-intensive higher education contexts: the scholarship of educational leadership / Harry T. Hubball, Anthony Clarke, Marion L. Pearson -- Educational administration and leadership in francophone Africa: 5 dynamics to change education / Boniface Toulassi -- Scholarly praxis at the edges: why responsible academic leadership matters in developing faculty scholarship / Linda Schwartz, Christina Belcher -- Increasing failure rates in Canadian university leadership: causes and solutions / Ross H. Paul -- Learning and space mean communication: theories rooting in China, India, and Europe / Gilbert Ahamer -- Investigating the roles of neuroscience and knowledge management in higher education / Kijpokin Kasemsap -- Ongoing and systematic academic program review / Neal Shambaugh -- Organizing digital production in a classic higher education institution: the case of the University of Salamanca / Fernando Almaraz-Menéndez, Alexander Maz-Machado -- The impact of social media on policy decisions in international higher education / Pamela A. Lemoine, P. Thomas Hackett, Michael D. Richardson -- English teaching and andragogy in transitioning students from secondary to higher education in China / Victor C.X. Wang, Theresa Neimann -- Language policy execution: the case of South African universities / Paul Hendry Nkuna -- Advancing women leaders in academe: creating a culture of inclusion / Cynthia Roberts --